2014
DOI: 10.1016/j.brs.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ultrasound-mediated Non-invasive Brain Stimulation: Examination of Sonication Parameters

Abstract: Background Transcranial focused ultrasound (FUS) has emerged as a new brain stimulation modality. The range of sonication parameters for successful brain stimulation warrants further investigation. Objective The objective of this study was to examine the range of FUS sonication parameters that minimize the acoustic intensity/energy deposition while successfully stimulating the motor brain area in Sprague-Dawley rats. Methods We transcranially administered FUS to the somatomotor area of the rat brain and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
237
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 255 publications
(273 citation statements)
references
References 37 publications
17
237
0
Order By: Relevance
“…Both the pulse duration and carrier frequency can be accommodated by current FDA guidelines—by using the time-average intensity and the mechanical index, respectively, as the limiting metrics. However, whether these exposure limits provide adequate guidelines for long-term neuromodulatory FUS—which appears to be capable of triggering plastic changes in neural circuits 26 —remains to be validated.…”
Section: Safety and Practicalitymentioning
confidence: 99%
“…Both the pulse duration and carrier frequency can be accommodated by current FDA guidelines—by using the time-average intensity and the mechanical index, respectively, as the limiting metrics. However, whether these exposure limits provide adequate guidelines for long-term neuromodulatory FUS—which appears to be capable of triggering plastic changes in neural circuits 26 —remains to be validated.…”
Section: Safety and Practicalitymentioning
confidence: 99%
“…Subsequent animal studies were implemented to characterize the effects of different FUS parameters on inducing functional neuromodulation [8,9]. Specifically, a recent study by Kim et al [10] showed the existence of an optimal pulsing scheme that elicits excitatory neural activity.…”
Section: Introductionmentioning
confidence: 99%
“…The stimulator circuit controls the parameters required for pulsed sonication, such as acoustic intensity, fundamental frequency, pulse repetition frequency, duty cycle, sonication duration, and interstimulus interval. (25) In addition, the stimulator circuit calculates the time delays for each transducer element as a function of the location of the target focal point. According to the calculated results, 32 time-delayed highvoltage bipolar pulses are generated in the stimulator circuit.…”
Section: Introductionmentioning
confidence: 99%